When crisis strikes: - Changes in work and professional identity among social workers in Norwegian Child Welfare Protection services during COVID-19 (Journal of Comparative Social Work, 2022)
When the COVID-19 pandemic reached Norway in March 2020, comprehensive action was taken by the government, leading to the lockdown of welfare institutions, schools and kindergartens, and strict restrictions on physical meetings. This had severe consequences for Child Welfare Protection services (CWP). The restrictions stopped child welfare protection home visits and professionals in other welfare institutions, which usually observe children and notify child welfare protection services, were no longer able to identify children at risk. This article, drawing on interviews with 10 social workers, explores their experience during COVID-19. Applying Lipsky’s concept of street-level bureaucrats and theories of professional identity, the article documents how COVID-19 not only restricted, but also modified social workers jobs, and led to self-reflection on their professional identity. In turn, the findings suggest the potential for beneficial changes in practices in the aftermath of COVID-19.